(untitled) (Colloquia Comparativa Litterarum, 2025)
Miloš Crnjanski, the Slavic Cultural Community and the Dialogue among Slavic Nations. Valentina Sedefceva. The Slavic theme in the novels by Miloš Crnjanski / Milos Tsernianski. Veliko Tarnovo, Universitetsko izdatelstvo „Sv. sv. Kiril i Metodiy“, 2017.